The relationship between light curing time, shear bond strength (SBS) and remanence index of adhesive (ARI) - Mahmoud El Saafin; Cristina Stanca Molnar; Irina Zetu; Daniela Manuc; Simina Neagoe; Mariana Pacurar (Amaltea Medical Publishing House, 2022)
The objective of this study is to investigate the effect of different light curing times on the shear strength and remanence index of the adhesive. The light curing intensity was presented by Woodpecker LED light curing unit (2500 mw/cm2). The study was performed on groups of extracted premolars: The first and second groups had a light-curing time of 3 seconds, and the third and fourth groups had a light-curing time of 6 seconds. However, the first and third groups were tested after 24 hours, and the second and fourth groups after 14 days. The study showed that increasing the light curing intensity, exposure time and the time after the brackets bonding will increase SBS and will decrease ARI on the other hand, using light curing unit (2500 mw/cm2) with 6 seconds light exposer will produce sufficient SBS, and 3 seconds light cure exposer (2500 mw/cm2) will produce insufficient SBS.